Kejadian Dismenore Primer Berdasarkan Tingkat Asupan Zat Besi, Asupan Kalsium, Aktivitas Fisik Dan Status Gizi Pada Mahasiswi Uhamka - Desiani Rizki Purwaningtyas; Liza Endah Andriyani; Fitria Fitria (ARGIPA (Arsip Gizi dan Pangan), 2023)
Primary dysmenorrhea is menstrual pain in the absence of genital abnormalities that appear in a person after their ovulation cycle has remained. The peak of the incidence of dysmenorrhea is in adolescence, which is 15-25 years. The purpose of this study was to determine the relationship between iron intake, calcium intake, and physical activity with primary dysmenorrhea in UHAMKA students. This research was a quantitative study with a cross-sectional design, and used univariate and bivariate data analysis.   The sample consisted of 289 people. The dependent variables in this study were primary dysmenorrhea while the independent variables in this study were iron intake, calcium intake, physical activity, and nutritional status. Dysmenorrhea data collection was taken using the WaLIDD Score questionnaire. Iron and calcium intake data were taken with the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) questionnaire. Physical activity data was taken using the International Physical Activity Questionnaire (IPAQ) questionnaire. Nutritional status indicator used BMI. The results showed that most of the subjects had primary dysmenorrhea and had insufficient intake of iron and calcium. More than half of the subjects had a moderate level of physical activity and normal nutritional status. The chi-square test showed that there was significant relationship between iron intake, calcium intake, and nutritional status, but there was no significant relationship between physical activity  with primary dysmenorrhea. Therefore, intake of iron and calcium must be increased and BMI must be maintained within normal category to prevent primary dysmenorrhea.